THE GSTP1 c.313A>G POLYMORPHISM MODULATES THE CARDIORESPIRATORY RESPONSE TO AEROBIC TRAINING - A Zarebska; Z Jastrzebski; M Kaczmarczyk; K Ficek; A Maciejewska-Karlowska; M Sawczuk; A Leońska-Duniec; P Krol; P Cieszczyk; P Zmijewski; N Eynon (Termedia Publishing House, 2014)
The GSTP1 c.313A>G polymorphism is a candidate to explain some of the individual differences in cardiorespiratory fitness phenotypes' responses to aerobic exercise training. We aim to explore the association between the GSTP1 c.313A>G polymorphism and the response to low-high impact aerobic exercise training. Sixty-six Polish Caucasian women were genotyped for the GSTP1 c.313A>G polymorphism; 62 of them completed 12-week aerobic (50-75% HR max ) exercise training and were measured for selected somatic features (body mass and BMI) and cardiorespiratory fitness indices - maximal oxygen uptake (VO 2max , maximum heart rate (HR max ), maximum ventilation (V Emax ) and anaerobic threshold (AT) - before and after the training period. Two-factor analysis of variance revealed a main training effect for body mass reduction (p=0.007) and BMI reduction (p=0.013), improvements of absolute and relative VO 2max (both p<0.001), and increased V Emax (p=0.005), but not for changes in fat-free mass (FFM) (p=0.162). However, a significant training x GSTP1 c.313A>G interaction was found only for FFM (p=0.042), absolute and relative VO 2max (p=0.029 and p=0.026), and V Emax (p=0.005). As the result of training, significantly greater improvements in VO 2max , V Emax and FFM were gained by the GG+GA group compared to the AA genotype group. The results support the hypothesis that heterogeneity in individual response to training stimuli is at least in part determined by genetics, and GSTP1 c.313A>G may be considered as one (of what appear to be many) target polymorphisms to influence these changes.